Variation in Chemical Constituents of Siyez Wheat (Triticum monococcum L.) in Response to Some Abiotic Stress Factors - Turfan, Nezahat; Sarıyıldız, Temel; Mutlu, Ekrem (My University, 2019)
Main aim of this study was to determine the effects of different salt contents (75 mM, 150 mM and 225 mM NaCl), heavy metal (0.2 mg/L FeCl3, NiCl2, ZnCl2), lime (2 mg/L CaCO3), drought (50%) and pollution (0.2 mg/L dust of factories) on photosynthetic pigments, malondialdehyde (MDA), hydrogen peroxide (H2O2) levels, the ascorbate peroxidase (APX), catalase (CAT), guaiacol peroxidase (GPOX) and superoxide dismutase (SOD) in Siyez wheat (Triticum monococcum L.). All experiments were carried out under laboratory conditions with 16 hour-day and 8 hour-night photoperiod in an incubator at 23 ± 1°C. Results showed that mean chlorophylla concentration was highest in the siyez seedlings treated with the pollution, while both mean chlorophyll-b and total chlorophyll concentrations were highest with 75 mM salt application. Mean total carotenoid was, however, highest with the drought treatment and mean relative water content was highest with NiCl2 application. Mean MDA and H2O2 contents were found to be highest in the siyez seedlings treated with 225 mM salt, whereas they were lowest with NiCl2 treatment. Mean proline content was highest with the NiCl2 treatment compared to the lowest concentration in the control siyez seedlings (82 µmol/g). Mean APX, CAT and GPOX activities were noted to be highest in the siyez seedlings treated with NiCl2. In general, the siyez seedlings showed high tolerance to the pollution, NiCl2 and drought with having highest photosynthetic pigments, proline, protein content and enzymes activities. Among all treatments, 225 mM NaCl and CaCO3 negatively influenced chemical compounds of the siyez seedling. When all data are taken into consideration, it can be said that higher photosynthetic pigments, proline contents, antioxidant enzymes activities and lower MDA and H2O2 levels play an important role in the resistance of siyez seedlings against abiotic stress conditions.

Bu çalışmanın esas amacı farklı konsantrasyonlarda tuz (75 mM, 150 mM ved 225 mM NaCl, ağır metal (0.2 mg/L FeCl3, NiCl2, ZnCl2), kireç (2 mg/L CaCO3), kurak (%50) ve kirlilik (0.2 mg/L fabrika baca tozu) uygulamalarının Siyez buğdayının (Triticum monococcum L.) fotosentetik pigment, malondialdehit (MDA), hidrojen peroksit (H2O2), prolin, toplam çözünür protein, askorbat peroksidaz (APX), katalaz (CAT), guaiakol peroksidaz (GPOX) ve süperoksit dismutaz (SOD) aktiviteleri üzerine etkilerini araştırmaktadır. Bulgulara göre klorofil a miktarı kirlilik uygulamasında, klorofil b ve toplam klorofil miktarı ise 75 mM tuz uygulamasında en yüksektir. Bununla birlikte toplam karotenoit kuraklık uygulamasında ve bağıl su içeriği de NiCl2 uygulamasında en yüksek değere ulaşmıştır. MDA ve H2O2 içeriği 225 mM tuz uygulamasında en yüksek, NiCl2 uygulamasında en düşüktür. Prolin içeriği kontrole göre (82 µmol/g) NiCl2 uygulamasında en yüksektir. APX, CAT ve SOD aktiviteleri NiCl2 uygulamasında yüksek olarak bulunmuştur. Sonuç olarak siyez fideleri yüksek pigment, prolin, protein ve enzim aktiviteleri ile kirlilik, NiCl2 ve kurak uygulamalarına yüksek tolerans göstermiştir. Uygulamalardan 225 mM tuz ve CaCO3 siyez fidelerindeki kimyasal bileşenleri negative olarak etkilemiştir. Tüm veriler göz önünde bulundurulduğunda yüksek fotosentetik pigment, prolin ve antioksiadant enzim aktiviteleri ve düşük MDA ve H2O2 miktarlarının siyezin abiyotik stres koşullarına toleransında önemli rol oynadığı söylenebilir.
Siyez Buğday Çeşidinin Kimyasal Bileşenlerinin Bazı Abiyotik Stres Koşullarına Karşı Değişimi
Keywords: [No Keywords]